2019
DOI: 10.3390/rel10030185
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences of Utilizing Religious and Spiritual Beliefs as Coping Resources After Miscarriage

Abstract: Religious and spiritual beliefs enable some bereaved women to cope better with the devastating effects of the loss of a baby through miscarriage. The aim of this study is to explore the experiences of women’s utilization of religious and spiritual beliefs as coping resources after miscarriage. Heideggerian interpretive phenomenological approach guided the study. Data were collected using audio-recorded, semi-structured interviews with 10 women and analyzed thematically using the method developed by van Manen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…I have a good memory of [my baby]. That helped me to find ways to adjust and move on knowing that the baby will always be part of my family” [( 91 ), p. 6]. The inference from this patient exemplifies how a provider's reserved but open communication style can support a patient's spiritual beliefs without imposing any religious maxims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I have a good memory of [my baby]. That helped me to find ways to adjust and move on knowing that the baby will always be part of my family” [( 91 ), p. 6]. The inference from this patient exemplifies how a provider's reserved but open communication style can support a patient's spiritual beliefs without imposing any religious maxims.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural and spiritual humility are conducive to superlative interpersonal communication and relational efficacy contributing to provider compassion satisfaction ( 88 ). Nurse researcher Kalu ( 91 ) concluded that religious and spiritual beliefs can support and promote better coping for individuals experiencing a reproductive loss. In her study done in Africa, one woman said, “The midwife sat and listened to me.…”
Section: Discussionmentioning
confidence: 99%
“…Nigeria is a multicultural, multireligious and multilingual country. To be able to provide holistic womencentred maternity care to all women, it is important that midwives understand and appreciate the roles of culture, religion, and spiritual beliefs in the lives of many individuals in Nigeria (34)(35). Being culturally competent will enable midwives to understand, appreciate, and interact with women from different cultural and religious backgrounds (35)(36).…”
Section: Issues With Access To Maternity Care Servicesmentioning
confidence: 99%
“…To be able to provide holistic womencentred maternity care to all women, it is important that midwives understand and appreciate the roles of culture, religion, and spiritual beliefs in the lives of many individuals in Nigeria (34)(35). Being culturally competent will enable midwives to understand, appreciate, and interact with women from different cultural and religious backgrounds (35)(36). The use of professional interpreter during antenatal education will also help to alleviate language and communication di culties experienced by the midwives and the women (37).…”
Section: Issues With Access To Maternity Care Servicesmentioning
confidence: 99%
“…In Nigeria, approximately 314,000 babies died from stillbirth in 2015 (Blencowe et al, 2016). Studies from Nigeria have reported that people generally interpret life circumstances through their traditional and religious beliefs (Adebayo et al, 2019;Kalu, 2019). However, in the context of stillbirth, the role of traditional and religious beliefs has been described as a 'double-edged sword' (Adebayo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%